MORFOLOGI DAN KEKERABATAN ANTARA Leopoldamys siporanus (THOMAS, 1985) DAN L. sabanus (THOMAS, 1987) (MURIDAE) ASAL KEPULAUAN MENTAWAI SUMATERA KALIMANTAN DAN JAWA - Ibnu Maryanto; M.H. Sinaga; K. Soebekti (The East Java Biological Society, 1999)
Jawa, Anamba, and Leopoldamys siporanus from Siberut and Pagai-Mentawai Islands was analyzed using discriminant analysis. The analysis showed that the morphological shape of Sumatran L. sabanus was an intermediate between Jawa and Kalimantan populations. The population of L. sabanus from Anamba Island was predicted to be closed to the intermediate from between Kalimantan and Sumatra. Specimens of L. siporanus from Siberut and Pagai indicated that their morphology was closer to that of L. sabarus from Kalimantan than it was from Sumatra or Jawa. In Sumatra L. sabarus has three subspecies which are distributed in northern side of West Sumatra (L.s. tapanulius), southern side of West Sumatra (L.s. ululans) and Mount Kerinci at Sumatra (L.s. vociferans). Furthermore, specimens examined in this study were collected from Leuser and Bengkulu where they are located at the corner of tapanulius and ululans type locality, and they were predicted as one population. This finding raises the possibility that the Sumatrans has one shape of L. sabanus, but this argument should be confirmed from prototype specimens of ululans, vociferans, and tapanulius.